A world in turmoil: governing risk, establishing order in humanitarian crises. (1st March 2019) - Dijkzeul, Dennis; Sandvik, Kristin Bergtora
Abstract : This special issue of Disasters on humanitarian governance focuses on risk and order. Its contributions show the tensions between humanitarian normative ideals and practical consequences, as many of the ordering effects are associated with either intended or unintended consequences. This introduction offers a conceptual framing of humanitarian governance. Defining humanitarian governance as a subset of global governance, the paper shows how humanitarians have attempted to improve the consequences of their work by fighting instrumentalisation and instituting rationalisation processes. It adapts four questions, originally formulated by Michael Barnett (2013 ), to examine the ways in which humanitarian governance functions in more detail: what kind of world is being imagined and produced through the specific concern with order and risk? Who governs? How is this a form of humanitarian governance and how is it organised? And finally, what are the principal techniques of such governance? The conclusion summarises the main findings and sets an agenda for further research.